Reactions of Bidentate Oxime and Quinoline Ligand with Antimony Trichloride Adducts with N-donors. - Rastogi, M.K. (Asian Journal of Chemistry, 2010)
Some nitrogen donor molecules form stable adducts with antimonytrichloride These adducts are allowed to react with dioximes,salicylaldoxime and 8-hydroxy quinoline in molar ratios 1 : 2 incold and in hot in THF solvent. Different products are obtainedunder two different conditions. In cold the oximes and 8-hydroxyquinolinesimply behave as mono acid ligands (except γ-benziJdioxime)and replace two of the chlorine atoms in the antimonytrichloride adducts. But in hot, one of the dioxime moleculesbehaves as diacid ligand while the other molecule as monoacidligand and replacement of all the three chlorine atoms takes place.Their structures are concluded from physical measurements andanalytical data.